School leadership challenges in the implementation of technical and vocational education curriculum in Ghana - Osei-Asibey, Daniel (2015)
Osei-Asibey Daniel. 2015. School Leadership challenges in the Implementation of Technical and Vocational Education Curriculum in Ghana. University of Jyvaskyla. Department of Education. ABSTRACT The purpose of technical and vocational education and training is basically to provide individuals with needed skills for socio-economic and industrial development. In most developing countries especially, TVET lays much emphasis on the kind of training that prepares the youth for self-employment. In Ghana like most developing countries, the aim of TVET is no different from the above. However, TVET in Ghana is bedeviled with a number of challenges ranging from limited funding, inadequate tools and equipment, obsolete and broken down facilities, lack of properly trained teaching and non-teaching staff to handle the programme, negative public perception and attitudes towards TVET and many others. This paper examines the challenges from the perspective of the school leadership in Ghana. It is aimed at unearthing the challenges facing TVET at the implementation level and ultimately finding a sustainable remedy in the future. To realize the aims of the study, qualitative case study was used. Three schools were specially selected. Focus group interviews with a total of eighteen respondents were used. The analysis was thematically carried out, and was mostly driven by the data. The results of the study most affirmed the challenges that have been highlighted by existing literatures. However, the study revealed some challenges which are either ignored or less talked about by the various stakeholders, yet the continuous existence of those challenges continue to hamper the efforts by the school leadership to address some of the fundamental challenges facing TVET in Ghana. In this paper, I recommend that efforts to redeem the image and to make TVET useful in Ghana be made to revolve around improvement of teacher training and provision of relevant tools and equipment for various TVET schools. I also recommended that a study be conducted into finding the solution to the challenges from the perspective of the school leadership.